Knowledge, attitudes, and practices of Texas hunters: a potentially high-risk population for exposure to the parasite that causes Chagas disease - Garcia, Melissa N (Parasit Vectors, 2015)
BACKGROUND: Chagas disease is a parasitic infection transmitted to humans and mammals by the Triatominae insect. If untreated, Chagas disease can lead to heart failure and death. Previous publications highlighted the potential public health risk of disease transmission among hunters in the United States. FINDINGS: We further investigated this population’s risk by administering a knowledge, attitudes, and practices questionnaire. Responses from hunters detailed the vector exposure and hunting practices unique to this population that might lead to their increased risk of disease transmission. CONCLUSIONS: Hunters should be aware of their potential risk for exposure to the insect that could be infected with the parasite that causes Chagas disease.